2020
DOI: 10.3390/ani10050850
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Bone Stability and Egg Production in Genetically Divergent Chicken Layer Lines

Abstract: Impaired animal welfare due to skeletal disorders is likely one of the greatest issues currently facing the egg production industry. Reduced bone stability in laying hens is frequently attributed to long-term selection for increased egg production. The present study sought to analyse the relationship between bone stability traits and egg production. The study comprised four purebred layer lines, differing in their phylogenetic origin and performance level, providing extended insight into the phenotypic variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
6
25
0
Order By: Relevance
“…Consistent with the literature [38], this research revealed considerable phenotypic differences in terms of bone traits between the genotypes. Our findings support the hypothesis that bone morphometry has only limited influence on bone breaking strength [9]. The results suggest the crossbreds being heterotic, as they showed enhanced values in comparison with the respective purebred parents [39].…”
Section: Comparison Of Genotypessupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the literature [38], this research revealed considerable phenotypic differences in terms of bone traits between the genotypes. Our findings support the hypothesis that bone morphometry has only limited influence on bone breaking strength [9]. The results suggest the crossbreds being heterotic, as they showed enhanced values in comparison with the respective purebred parents [39].…”
Section: Comparison Of Genotypessupporting
confidence: 87%
“…While the majority of studies have investigated bone stability in contemporary laying hybrids, the number of such studies conducted in local chicken breeds is very limited. However, it was found that bone characteristics differ considerably between genotypes [9], which is why findings from high performing lines can probably not fully be transferred to local breeds. So far, there has been little discussion about how purebred local chicken breeds and their crossbreds differ in terms of bone characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The diaphyseal cortical bone proportion ("cortical area") of the left tibiotarsus cut surface was assessed planimetrically [28]. The right long bones were used for assessing bone breaking strength (N) via a three-point bending test as described by Jansen et al [22]. At slaughter, the keel bones were visually examined for the presence of fractures, indicated by fracture lines or callus formation.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment included four purebred chicken layer lines (Gallus gallus domesticus) differing in terms of egg production performance and phylogenetic origin, two white-egg layers and two brown-egg layers. The high performing lines WLA and BLA originate from a commercial breeding program (Lohmann Tierzucht GmbH, Cuxhaven, Germany) and achieve an annual egg production of about 316 eggs [22]. The moderately performing lines R11 and L68 are maintained as resource populations without any selection at the Institute of Farm Animal Genetics of the Friedrich-Loeffler-Institut (Neustadt, Germany) and achieve a laying performance of 226 (R11) and 216 (L68) eggs per year.…”
Section: Animals and Housingmentioning
confidence: 99%
See 1 more Smart Citation